![Slide8.JPG](https://cdn.teachoo.com/c83e7d24-da89-4073-a6de-c086e9e0332a/slide8.jpg)
![Slide9.JPG](https://cdn.teachoo.com/b9de38ba-e6db-4bb6-ba90-ce6bb92dfa86/slide9.jpg)
![Slide10.JPG](https://cdn.teachoo.com/e74a9d16-a040-47f7-a323-71d078fde4d2/slide10.jpg)
Geometric Progression(GP): Formulae based
Geometric Progression(GP): Formulae based
Last updated at Dec. 16, 2024 by Teachoo
Ex 8.2, 3 The 5th, 8th and 11th terms of a G.P. are p, q and s, respectively. Show that q2 = ps. We know that an = arn – 1 where an = nth term of GP n is the number of terms a is the first term r is the common ratio Here, 5th term is p i.e. a5 = p Putting n = 5 in an formula p = ar5–1 p = ar4 Also, 8th term is q i.e. a8 = q Putting n = 8 in an formula q = ar8 – 1 q = ar7 Also, 11th term is s i.e. a11 = s Putting n = 11 in an formula s = ar11 – 1 s = ar10 We need to show that q2 = ps. Taking L.H.S q2 Putting value q = ar7 from (2) = (ar7)2 = a2r14 Now, solving R.H.S ps Putting p = ar4 , s = ar10 from (1)& (3) = (ar4) (ar10) = (a × a)(r10 × r4) = a2r14 = L.H.S Thus, L.H.S = R.H.S Hence proved